Multisensory Experiential Tourism Strategies in Guangxi, China - Na, Quan; Nurmalinda, Elda; Rianto, Rianto; Djati, Sundring Pantja; Rahmanita, Myrza (Jurnal Penelitian Pariwisata, 2024)
Analyzing the affecting factors of experiential tourism, the study aims to explore the innovational strategies for multisensory experiential tourism. The adopted research methods are qualitative research and case study, which make a comparison between the boom of ice-snow tourism in Harbin city, northeast China, and its interactive partner, Guangxi, southwest China, in Jan. 2024. Analyzing the innovational tourism phenomena of the 33 pieces of related news online in China Daily, the data is collected and a framework of multisensory experiential tourism strategies was drawn up. With the influential factors of multisensory experiential tourism, such as sight, hearing, smell, taste, and touch, ice and snow tourism in Harbin made a hit. In conclusion, by building up sustainable smart destinations, experiencing the different lifestyle, and highlighting study tour activities, it is hoped to put forward a framework of multisensory experiential tourism strategies for Guangxi, based on its unique leisure tourism resources. Keywords: tourism strategy, multisensory experiential, innovation, Harbin, Guangxi